(untitled) - Romana, Manuel (London, 2007)
This book contains papers and special lectures presented at the workshop Underground works under special conditions held in Madrid in 2007, within the framework of the 11th international Congress of the international Society for Rock Mechanics. It contains a comprehensive collection of topics related to some of the most complex underground works recently undertaken across the world. A number of main themes are highlighted in the book: rock burst, face stability, design parameters and TBM selection criteria, among others.
Keywords: Underground engineering,Kỹ nghệ xây dựng